Volatility Drivers in Islamic Stock Markets: The Case of IDX30 Index Firms in Indonesia - Anggas Arden Arya Satya; Mahatir Muhammad (Yayasan Mitra Peduli Indonesia, 2026)
Stock price volatility is a crucial phenomenon in the capital market as it reflects the degree of price instability that directly affects investment decisions. This study aims to analyze the effect of firm size, profitability, leverage, and free float ratio on stock price volatility. A quantitative approach is employed using panel data regression analysis in EViews 12. The research sample consists of 12 companies selected purposively from the companies listed in the IDX30 index on the Indonesia Stock Exchange during the 2020–2024 period. The results show that, to some extent, firm size and profitability significantly affect stock price volatility. Then, leverage and free float ratio do not have a significant effect. However, simultaneously, all four independent variables significantly influence stock price volatility. These findings provide empirical contributions to investors and capital market participants by identifying key fundamental factors that influence stock price fluctuations.